East and Southern Africa Forest Observatory: Fostering regional data sharing - Center for International Forestry Research; Regional Centre For Mapping Of Resources For Development (Center for International Forestry Research, 2021)
The objective of the observatory is to produce a comprehensive and harmonized regional dataset on the latest trends and threats to forests, and to make information useful and easily accessible to policymakers, funders, forestry practitioners and citizens.